2021
DOI: 10.1038/s41405-021-00084-3
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and oral health behavior in young adults with caries disease

Abstract: Objective The aim of this study was to describe and analyze oral health, oral health behaviors, and oral health-related quality of life (OHRQoL) in relation to the level of caries disease among caries-active young adults. Material and methods This study presents data from a sample of young adults (n = 135) with active caries disease who were enrolled in a clinical, randomized controlled trial. The independent variables of sociodemographics, oral he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…In children, irregular dental attendance was associated with DMFT [ 7 , 122 , 206 ] and poor OHRQoL [ 207 ]. In 13 studies of adults, irregular dental attendance was associated with poor oral health (e.g., DMFT and self-report of poor oral health) [ 8 , 56 , 66 , 96 , 100 , 125 , 135 , 160 , 167 , 169 , 171 , 208 , 209 ]. One study reported no significant association between dental attendance and change in OHRQoL over a 12-month period in adults [ 210 ].…”
Section: Resultsmentioning
confidence: 99%
“…In children, irregular dental attendance was associated with DMFT [ 7 , 122 , 206 ] and poor OHRQoL [ 207 ]. In 13 studies of adults, irregular dental attendance was associated with poor oral health (e.g., DMFT and self-report of poor oral health) [ 8 , 56 , 66 , 96 , 100 , 125 , 135 , 160 , 167 , 169 , 171 , 208 , 209 ]. One study reported no significant association between dental attendance and change in OHRQoL over a 12-month period in adults [ 210 ].…”
Section: Resultsmentioning
confidence: 99%
“…So far, the focus has been on the investigation of vulnerable target groups who already suffer from mental disorders such as depressive disorders or eating disorders (see Introduction). However, more recent studies conducted in samples of young healthy adults in several countries point to an interesting paradox of better subjective oral health in the elderly compared with young or middle-aged adults (Hagman et al, 2021 ). Given the prominence and increasing prevalence of depression and eating disorders in the general population, particularly in the population of young adults, the present studies thought to answer whether oral health impairments and mental health conditions, predominantly related to depressive symptoms and symptoms related to eating disorders are already linked in healthy young adults without clinical diagnosis of depression or eating disorders and without full blown oral diseases such as tooth loss, caries or periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…In 2021 alone, there were eight papers published on the experience of patients, 7,8,9,10,11,12,13,14 again from a wide geographical reach including Lima, 11 Malaysia 7 and India. 13 Of these eight, three papers focused on the health and oral health of older adults.…”
Section: Patient Experiencementioning
confidence: 99%